Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11606-013-2553-7
|View full text |Cite
|
Sign up to set email alerts
|

Body-Mass Index and All-Cause Mortality in US Adults With and Without Diabetes

Abstract: BACKGROUND: Previous studies found normal weight compared to overweight/obese adults with type 2 diabetes had a higher mortality risk, and body-mass index (BMI)-mortality studies do not typically account for baseline diabetes status. OBJECTIVE: To determine if diabetes influences the BMI-mortality relationship. DESIGN: Using a prospective study design, we analyzed data from a nationally representative sample of US adults participating in the National Health Interview Survey from 1997 to 2002, and followed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 42 publications
2
76
1
1
Order By: Relevance
“…Grey shading indicates 95% CI smokers in both Black and White participants [41]. In comparison Jackson and colleagues did not find a variation in the association between BMI and mortality by smoking status [30]. Our findings showed a nonlinear relationship between BMI and all-cause mortality in people with diabetes, with the lowest risk around 33 kg/m 2 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Grey shading indicates 95% CI smokers in both Black and White participants [41]. In comparison Jackson and colleagues did not find a variation in the association between BMI and mortality by smoking status [30]. Our findings showed a nonlinear relationship between BMI and all-cause mortality in people with diabetes, with the lowest risk around 33 kg/m 2 .…”
Section: Discussioncontrasting
confidence: 56%
“…1). Following detailed assessments, and after the inclusion of three articles identified from manual searches, 21 articles were included in the quantitative analysis (21 studies and 24 unique cohorts; Table 1) [7,8,11,15,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Study characteristics and the NOS scores are provided in ESM Tables 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Jackson et al 7 indicates that mortality increases with increasing BMI in adults without diabetes, but decreases with increasing BMI among their counterparts with diabetes. Their finding in diabetic patients might be of particular interest to developers of practice guidelines for the American Diabetes Association, and might also support the recent finding from the Look AHEAD (Action for Health in Diabetes) study.…”
mentioning
confidence: 98%
“…Most previous studies did not exclude patients with a history of CVD and cancer when they assessed the association between BMI and the risk of mortality among individuals with type 2 diabetes. [4][5][6] The analysis by Jackson et al 7 excluded individuals who reported a prior history of cancer and/or coronary heart disease, which can minimize the influence of reverse causation.…”
mentioning
confidence: 99%
See 1 more Smart Citation